An Insight into Indigenous Ethnobotanical Knowledge of Medicinal and Aromatic Plants from Kashmir Himalayan Region - Gillani, Syed Waseem; Ahmad, Mushtaq; Ahmad, Mushtaq; Ahmad, Mushtaq; Zafar, Muhammad; Haq, Sheikh Marifatul; Waheed, Muhammad; Muhammad Manzoor; Shaheen, Hamayun; Sultana, Shazia; Rehman, Fazal Ur; Makhkamov, Trobjon (Ethnobotany Research and Applications, 2024)
Background: Documenting traditional knowledge of medicinal plants has enabled researchers to obtain a good understanding of the consumption patterns of plants for basic healthcare purposes. This study highlighted the ethnobotanical significance of medicinal and aromatic plants in the biodiversity hotspot landscape of the western Himalayan region of Kashmir. Methods: Extensive field visits were made to collect traditional ethnobotanical knowledge from the study area through group discussions in the local language using the questionnaire method. The acquired data was then analyzed using quantitative ethnobotanical measures such as Use Value (UV) and Relative Frequency of Citation (RFC). Results: Our findings revealed 72 plant species belonging to 51 genera and 16 families. The dominant families recorded were Lamiaceae and Apiaceae followed by Polygonaceae. Among plant parts, leaves were the most frequently used, followed by roots. The majority of the studied plants were herbaceous, accounting for 90.3% of the area flora. Based on the medicinal plant use category, 72 plant species with medicinal uses were identified. According to the Use Value and Relative Frequency Citation, Saussurea costus and Angelica cyclocarpa had remarkably high values of 1.38 and 0.68, respectively. Conclusions: These findings complement the considerable plant knowledge of the local population, confirming the traditional usage of plants in indigenous healing. People in Muzaffarabad continue to have vital information about native flora, even though younger individuals are losing it as a consequence of socioeconomic changes. There is a need to raise awareness among local populations about the sustainable use and conservation of medicinal flora. Keywords: Medicinal plants, Kashmir Himalayas, Field survey, Ethnobotanical knowledge, Aromatic plants